Residual Analysis of Aflatoxins in Spice by HPLC Coupled with Solid-Phase Dispersive Extraction and Solid-Phase Fluorescence Derivatization Method. (15th July 2020) - Saito, Koichi; Ishii, Junki; Naniwa, Misaki; Ishii, Rie; Kato, Mihoko; Kondo, Takahide; Sakurai, Hikaru; Taniguchi, Masaru; Hashiguchi, Shigeki; Hayashi, Takako; Ito, Rie
Abstract: Background: Aflatoxins (AFs) are carcinogenic mycotoxins. A simple, quick, and accurate method for the micro-analysis of AFs in foodstuffs, especially spices, is needed. Objective: A sophisticated pretreatment method that combines solid-phase dispersive extraction (SPDE) and solid-phase fluorescence derivatization using immunoaffinity (IA) gel as the solid phase was developed to analyze AFs in spices simply, quickly, and sensitively by liquid chromatography with fluorescence detection. Method: White and black pepper samples were extracted with a mixed solution of methanol/water (4:1) and then diluted with 7% aqueous solution of Triton-X. The solution was subjected to cleanup by SPDE using IA gel. Trifluoroacetic acid was added to the IA gel for on-site solid-phase fluorescence derivatization. Results: Chromatograms containing well-separated peaks and few interference peaks from contaminants were obtained. The method detection limit of AFs in white and black pepper was 0.15–0.29 ng/g. Repeatability and intermediate precision were <10% and <15%, respectively, and accuracy was 61.7–87.8%. In addition, inter-laboratory precision was <29% and mean recovery was 61.5–76.7%. A favorable z -score of | Z | ≦ 1 was obtained in seven laboratories, although one laboratory gave 2 < | Z | < 3. Conclusions: The validity, reliability, practicality, and robustness of the developed method were verified. Highlights: By using SPDE and solid-phase fluorescence derivatization in combination for AF analysis, fluorescence derivatization during cleanup was realized, leading to simplification of the pretreatment operation.